Development and tests of a thrust stand with an in-situ null position adjustment and calibration method for low power plasma thrusters - Ugur Kokal; Emin Saridede; Murat Celik (Results in Engineering, 2023)
A growing number of space missions use electric propulsion systems due to their higher specific impulse and greater efficiency compared to chemical propulsion systems. Because they are able to generate relatively low thrust values, conventional thrust measurement mechanisms used for chemical propulsion systems can not be used for electric propulsion systems. Thus, millinewton level thrust measurement systems are needed to be developed for measuring the low-level thrust of these types of thrusters. At the Bogazici University Space Technologies Laboratory (BUSTLab), a double inverted pendulum type thrust stand with a changeable thrust measurement range between 6 mN – 300 mN was designed, built and tested. The measurement resolution of this thrust stand can be as low as 100 μN level and it can be adjusted by changing the flexure stiffness and the mass of a counterweight. This study investigates the BUSTLab thrust measurement system and its key design points, with a particular focus on its in-situ null position adjustment and calibration process, and methods for mitigating external perturbations during thrust measurements.